2018
DOI: 10.1002/aic.16137
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide chemical absorption by solvents based on diamine and amines blend

Abstract: Present work includes research about the influence of the type of amino group using one or two amine molecules on carbon dioxide chemical absorption using aqueous solutions of alkanolamines and diamines. A comparison of chemical absorption processes using aqueous solutions of two individual diamines (3‐(dimethylamino)propan‐1‐amine and 1,3‐diaminopropane) and a mixture of amines (3‐amino‐1‐propanol and 3‐(dimethylamino)propan‐1‐ol) is reported including absorption rate curves, carbon dioxide loading, reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This work shows fast kinetics and low energy requirements that indicate this type of solvents as promising ones. A previous work 18 of our team showed that a diamine allows to reach similar values that amines blend for absorption rate and carbon dioxide loading. Diamines have also shown suitable characteristics as activator for carbon dioxide chemical absorption 19 and lower heat of absorption than commonly used amines 20 …”
Section: Introductionmentioning
confidence: 78%
“…This work shows fast kinetics and low energy requirements that indicate this type of solvents as promising ones. A previous work 18 of our team showed that a diamine allows to reach similar values that amines blend for absorption rate and carbon dioxide loading. Diamines have also shown suitable characteristics as activator for carbon dioxide chemical absorption 19 and lower heat of absorption than commonly used amines 20 …”
Section: Introductionmentioning
confidence: 78%
“…Preliminary research studies show that adding amines can reduce the viscosity of ILs, resulting in faster absorption and mass transfer. Especially, the absorption of CO 2 can be enhanced by constructing mixed absorbents of ILs plus amine due to the good affinity between amine and CO 2 . After extensive studies, DMAPA as an organic amine has a unique advantage in absorbing CO 2 . In particular, DMAPA-based ionic liquids can effectively absorb CO 2 through intramolecular proton transfer .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the benchmark industrially demonstrated process for post-combustion CO 2 capture technology from power plants is amines solvent-based absorption. However, high energy is required in the regeneration process and the corrosive and volatile nature of the amines also presents problems [10,11]. Physisorption of CO 2 into microporous materials has been widely studied in recent years.…”
Section: Introductionmentioning
confidence: 99%